FACTORS INFLUENCING THE INTENTION OF BEHAVIOR IN USING GOPAY MOBILE PAYMENT - Turangan, Joyce A.; Ruslim, Herman (International Journal of Application on Economics and Business, 2023)
At present, the development of technology and the internet is advancing rapidly and continues to grow from year to year. The number of smartphone and internet users is also increasing, leading to more frequent use of mobile payment applications. The use of mobile payment applications has several advantages, such as accelerating transactions and facilitating cashless payments. One of the applications used for mobile payment is GoPay, alongside other options such as OVO, Shopee, Dana, and other mobile payment platforms. The researcher aims to analyze the perception of the community towards GoPay as an electronic payment method using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach, which explains user behavior toward information technology based on social influence, performance expectancy, effort expectancy, and facilitating conditions. Each determinant is then tested against behavioral intention. This study has four hypotheses that will be tested, and the data collected for this research is obtained through respondent answers from questionnaires. The data is analyzed using Partial Least Square (PLS) analysis with Smart-PLS software, and the research results indicate that all variables have a positive and significant influence on behavioral intention.